The Influence and Significance of the Jurisprudence of the Constitutional Court on the Formation of Modern Criminal Policy - Gutauskas, Aurelijus (Vilnius University Open Series, 2024)
The aim of this article is to review some of the (more important) aspects of the jurisprudence of the Constitutional Court and its influence on the formulation of the modern criminal policy. It assesses the relationship between the quality of criminal laws and the impact of the Constitution on their enactment, the content of the constitutional conditions for the restriction of individual rights, and the influence of the Constitutional Court’s jurisprudence on the modern cassation process.
Keywords: Constitutional Court; constitutional principles; Constitutional Court rulings; Cassation Court